217k views
3 votes
I need help with a question

User HiveHicks
by
6.0k points

1 Answer

3 votes

We have the function:


y=-(2)/(3)x+7

When we have the value of x, and we want to find the value of y, we replace x in the equation and calculate.

For x=-6, we have:


y=-(2)/(3)\cdot(-6)+7=(-2\cdot6)/(3)+7=-(12)/(3)+7=-4+7=3

The value of y for x=-6 is y=3.

When we know y, and we want to know the value of x, we replace y and calculate.

For y=5, we have:


\begin{gathered} 5=-(2)/(3)x+7 \\ 5-7=-(2)/(3)x \\ -2=-(2)/(3)x \\ x=-2\cdot(-(3)/(2))=(2\cdot3)/(2)=3 \end{gathered}

For y=5, the value of x is x=3.

We repeat this for the last two cases:

x=15, the value of y is y=17


y=-(2)/(3)(15)+7=10+7=17

y=15, the value of x is x=-12


\begin{gathered} 15=-(2)/(3)x+7 \\ 15-7=-(2)/(3)x \\ 8=-(2)/(3)x \\ 8\cdot3=-2x \\ 24=-2x \\ x=(24)/(-2)=-12 \end{gathered}

User Malta
by
6.1k points